Maine’s Paradoxical Politics - Palmer, Kenneth (Maine Policy Review, 2010)
Kenneth Palmer’s article, based on his 2009 University of Maine College of Liberal Arts and Sciences Maine Heritage Lecture, discusses the paradoxes of Maine’s politics that often draw national attention. He notes how these paradoxes have contributed to the state’s having a “creative and effective political system.” Maine politics are dynamic in nature, with parties loosely hung together, governors winning by pluralities rather than majorities, and significant turnover both in members and parties in legislative districts. Palmer suggests that Maine’s political leaders find themselves as centrists, primarily because they want to find practical solutions to difficult problems.
Keywords: Maine; Maine politics; public policy